Hydrodistillation and soxhlet extraction of agarwood leaf extract from aquilaria malaccensis - Saripah Salbiah Syed Abdul Azziz (Tanjong Malim, 2019)
Hydrodistillation and soxhlet extraction of agarwood leaf extract from aquilaria malaccensis by Saripah Salbiah Syed Abdul Azziz